A challenging case of spontaneous idiopathic omental infarction in a trisomy 21 patient. (June 2022) - Roy, Aaron; Mah, Jin-Jiun; Ambikapathi, Theiyallen; Mra, Aung; Hayati, Firdaus
Abstract: Background: Omental infarction (OI) is a rare cause of acute abdominal pain that is often missed out. Due to its non-specific presentation can mimic other commoner conditions such as acute appendicitis, acute diverticulitis, and tuberculosis abdomen. Case presentation: We present a 42-year-old gentleman with trisomy 21 presenting right iliac fossa pain. Examination revealed tenderness in the right lower quadrant and blood parameters showed leucocytosis. With an initial impression of acute appendicitis, the patient was subjected to surgery. Intraoperatively, there were abnormalities to the omentum suggestive of OI, resulting in partial omentectomy. Symptom resolution occurred immediately and the patient was discharged early. Conclusion: OI is a rare cause of acute abdomen that can mimic other abdominal pathologies. In trisomy 21 patients who present with acute abdomen, thorough assessments including preoperative imaging are advisable. Diagnostic laparoscopy is recommended as OI can be managed via minimally invasive surgery, hence ensuring good surgical outcomes. Highlights: Omental infarction (OI) is a rare cause of acute abdominal pain that is often misdiagnosed, especially among those who present with right iliac fossa pain. In trisomy 21 patients who present with acute abdomen, thorough assessments including preoperative imaging are advisable. Diagnostic laparoscopy is recommended as OI can be managed via minimally invasive surgery, hence to ensure good surgical outcomes.